Urbanization and the Change in Political Elites - Raphaël Franck; Victor Gay (Global Labor Organization (GLO), 2024)
This study argues that urbanization changed the relationship between the occupation of candidates running in parliamentary elections and their electoral success. To identify local-level variation in urbanization, we leverage exogenous changes to the boundaries of electoral constituencies in the 1928, 1932, and 1936 French parliamentary elections. The results suggest that urbanization was detrimental to the electoral success of lawyers but beneficial to that of employees and workers. This electoral effect of urbanization was especially felt on the left of the political spectrum, whereby left-wing employees and workers crowded out left-wing lawyers.
Keywords: D72; K16; N44; N94; 330; Elections; Political Representation; Urbanization